Symbolic Communication Offerings in the Bancaan Bayi Ceremony: A Roland Barthes Semiotic Analysis in The Kediri, East Java - Tya Resta Fitriana; Kenfitria Diah Wijayanti; Budi Waluyo; Astiana Ajeng Rahadini; Winda Dwi Lestari; Favorita Kurwidaria; Prima Veronika (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to describe and analyze the symbolic communication that contains the names and forms of culinary offerings in the traditional Bancaan Bayi ceremony for believers in Kediri, and how these symbols are understood by the local religious community in the context of intercultural communication. The study uses a qualitative narrative method, observation, interview, and document analysis techniques. The data consists of the names and representations of culinary offerings, which are treated as cultural signs and communication media both with other humans and symbolic communication with God. The findings show that each type of offering contains symbolic messages regarding prayers, hopes, and salvation values that are negotiated through the process of ritual communication. Through Barthes's semiotic perspective, offerings function not only as cultural symbols but also as a form of spiritual and social communication that allows for the exchange of meaning between people from different religious backgrounds. Thus, Bancaan Bayi becomes an arena for intercultural communication that reproduces social harmony through culinary symbolism. This research has implications for supporting interfaith inclusion, thereby encouraging social sustainability and cohesion among community groups.